The incidence and implications of clouds for cloud forest plant water relations. (6th December 2012) - Goldsmith, Gregory R.; Matzke, Nicholas J.; Dawson, Todd E.; Penuelas, Josep
Abstract Although clouds are the most recognisable and defining feature of tropical montane cloud forests, little research has focussed on how clouds affect plant functioning. We used satellite and ground‐based observations to study cloud and leaf wetting patterns in contrasting tropical montane and pre‐montane cloud forests. We then studied the consequences of leaf wetting for the direct uptake of water accumulated on leaf surfaces into the leaves themselves. During the dry season, the montane forest experienced higher precipitation, cloud cover and leaf wetting events of longer duration than the pre‐montane forest. Leaf wetting events resulted in foliar water uptake in all species studied. The capacity for foliar water uptake differed significantly between the montane and pre‐montane forest plant communities, as well as among species within a forest. Our results indicate that foliar water uptake is common in these forest plants and improves plant water status during the dry season.